Laser patterning of amorphous silicon thin films deposited on flexible and rigid substrates - Alpuim, P. (2016)
The possibility of direct writing thin semiconductive channels and structures on insulating substrates in a clean room-free process is attractive for its simplicity, cost effectiveness, and possibility of a wide choice of substrates. A broad range of applications, such as large-area electronic devices (touch screens, flexible displays), sensors, or optical wave guides could benefit from such a process. In this work, we directly write on doped hydrogenated amorphous silicon (a-Si:H), with thickness in the range 10 nm–1 μm, using a Nd-YAG laser operating at 532 nm that is part of a Witec Raman confocal system. The contrast in conductivity between the exposed and unexposed areas is so high that the a-Si:H matrix needs not to be removed after exposure. B- and P-doped films were deposited on plastic, glass, and oxidized silicon wafers. The laser power threshold for crystallization was studied. The highest conductivity (886 Ω−1 cm−1) was obtained on wafer. On hard substrates, it is possible to tune the mesoscopic electrical conductivity in a very broad range of values (∼10−4–103) by design of the pattern to be transferred. Patterned films are piezoresistive with gauge factors as high as +18 and −29 for p- and n-type patterns, respectively. SEM image of laser written lines on a 10 nm thick a-Si:H film deposited on a Si/SiO2 substrate. Four regions are clearly distinguishable: the metal contact on the top area; the laser eroded area (lines); the crystallized areas adjacent to lines; the amorphous region at the bottom right.